THE RELATIONSHIP OF MINDFULNESS WITH THE LEVEL OF DEPRESSION IN ADOLESCENTS WITH SINGLE PARENTS - Apriliyani, Ita; Arni Nur, Rahmawati; Maryanto, Maryanto (Universitas Airlangga, 2024)
Introduction: Single-parent adolescents are often prone to depression. Depression itself is a natural disorder of feelings, emotions that a child or teenager can experience during the ransition from children to adults which is theresult of separation or loss of parents either due to divorce or death. Mindfulness can serve to increase one's sensitivity to understand current events. Method: This is a descriptive research analysis with a cross sectional approach. The independent variable of this study is the level of depression of students with single parents and the dependent variable is mindfulness. The population in this study was students with single parents at SMK Muhammadiyah Bumiayu. Sampling was carried out using a total sampling technique of 60 respondents by filling out the Mindful Attention Awareness Scale and Depression Anxiety Stress Scale (DASS) questionnaires. The analysis used was univariate and bivariate with bivariate assays of the characteristics of sex respondents using Spearman Rank. Results: The results showed that there was a relationship between mindfulness and depression levels of adolescents with single parents with a p value of 0.01. The results of student depression rates under normal conditions were 39 (65%), moderate depression 13 (21.7%), and mild depression 8 (13.3%). Conclusion: Adolescents with single parents who are depressed should strive to be able to achieve a state of mindfulness, so that adolescents are able to live and adapt their lives well. Keywords: mindfuleness, depression, adolescence